Association Of Peripheral Visfatin Levels And Visfatin G-948T Gene Polymorphism With Alzheimer's Disease In A Turkish Population - Vurgun, Ufuk; Şahin, Özlem; Tüfekçi, Kemal Uğur; Keskinoğlu, Pembe; Yener, Görsev; Genç, Kemal Kürşad; Genç, Sermin (Güneş Kitabevi Ltd Sti, M Rauf Inan Sok No 3, Ankara, Sıhhıye 06410, Turkey, 2013)
Introduction: Visfatin is a pleiotropic cytokine implicated in several physiological and pathophysiological processes such as innate immunity, cellular metabolism, longevity, and inflammation. Altered visfatin levels and visfatin gene polymorphisms have been reported in various human diseases, including type 2 diabetes mellitus, rheumatoid arthritis, obesity, coronary artery disease and stroke.. Materials and Method: In this study, we investigated whether serum visfatin levels were changed in volunteers with Alzheimer's disease (AD) (n = 40) or healthy controls (n=40) and whether visfatin gene G-948T polymorphism was associated with the disease. Results: Visfatin levels were not significantly different in AD patients compared with healthy aged control subjects. In this relatively small population, we found a significant, but weak association between GT heterozygous genotype at position -948 of visfatin gene and AD. However, there was no association between G-948T polymorphism and visfatin levels, and any demographic, anthropometric or biochemical parameters. Conclusion: Further studies in larger and different populations are needed to fully elaborate the involvement of visfatin gene in AD.
Keywords: Nicotinamide Phosphoribosyltransferase; Alzheimer Disease; Polymorphism; Inflammation; Aging; Colony-Enhancing Factor; Ischemic-Stroke; Plasma-Levels; Type-2; Obese; Inflammation; Promoter